2012
DOI: 10.1177/1359104512467273
|View full text |Cite|
|
Sign up to set email alerts
|

Nonsuicidal self-injury in an adolescent population in Singapore

Abstract: This mixed methods study examined the phenomenon of nonsuicidal self-injury (NSSI) of adolescents in Singapore. The researchers analyzed quantitative data to understand the functions of NSSI, the relationship of parental invalidation to NSSI, and the association between academic stress and parental invalidation. In addition, the researchers employed semi-structured qualitative interviews to provide supportive qualitative data. The participants were outpatients at the Child Guidance Clinic, Singapore, between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 42 publications
1
44
0
7
Order By: Relevance
“…This resonates with previous research which mainly supports an affect regulating function of NSSI [36]. In fact, similar results were obtained in previous studies done in a community sample in Singapore [24] and Sweden [39]. On the other hand, "to punish self" serves the SNR function and this supports the findings of previous research which found that self-directed anger, shame, and hatred predicted NSSI acts [40].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This resonates with previous research which mainly supports an affect regulating function of NSSI [36]. In fact, similar results were obtained in previous studies done in a community sample in Singapore [24] and Sweden [39]. On the other hand, "to punish self" serves the SNR function and this supports the findings of previous research which found that self-directed anger, shame, and hatred predicted NSSI acts [40].…”
Section: Discussionsupporting
confidence: 92%
“…Previous research done on NSSI amongst adolescents in Singapore examined the characteristics, functions and correlates of non-suicidal self-injury within a small clinical sample [24]. As for research on suicidal behavior, a cross-sectional epidemiological study conducted previously to examine socio-demographic and clinical correlates of suicidal behavior amongst Singapore residents aged 18 and above found the prevalence of suicide ideation, plan and attempt amongst those with lifetime major depressive disorder to be 43.6%, 13.7% and 12.3%, respectively [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although self-injuring youth typically report conflict in both family and peer relationships (Lundh et al, 2009) researchers suggest that a history of conflict with caregivers may play a key role in the emergence of NSSI behavior through the development of poor emotion regulation skills, and that conflict with peers may serve to maintain existing NSSI behavior (Crowell et al, 2009). Specifically, caregiver emotional invalidation, conceptualized as parenting practices which imply the child’s opinions and emotions are invalid, irrational or unimportant (Linehan, 1993), have been linked to emotion dysregulation and NSSI (Adrian et al, 2011; Sturrock and Mellor, 2014; Tan et al, 2014; Yurkowski et al, 2015). Indeed, when accounting for multiple interpersonal characteristics, retrospective self-reports of experiencing maternal antipathy has been shown to be the sole significant predictor of NSSI behavior (Kaess et al, 2013), and observed maternal emotional invalidation and coerciveness have been linked to greater conflict in interactions between adolescent self-injurers and their mothers (Crowell et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is also clear that NSSI is an international phenomenon, having been studied in Turkey [21], Hong Kong [25,26], Singapore [27], Austria [19], Belgium [28], Germany [17,18,19], Italy [29,30], the Netherlands [30], Switzerland [19], Hungary [31], Norway [32], Sweden [33], Iceland [34] and Australia [23,35], in addition to the USA and Canada.…”
Section: Prevalence Of Nssimentioning
confidence: 99%